Living Alongside: Teacher Educator Experiences Working in a Community-Based Aboriginal Teacher Education Program - Kitchen, Julian; Hodson, John (Canadian Journal of Education/Revue canadienne de l'éducation, 2013)
Aboriginal education in Canada needs to shift away from the assimilative model to a model of culturally responsive pedagogy. Teacher education programs that serve Aboriginal teachers have an important role to play in developing an education system that both meets mainstream and Indigenous criteria for success. This paper examines the experiences of teacher educators working in a community-based Aboriginal Bachelor of Education program that was developed through a university-community partnership. Through interviews with eight teacher educators working in the program, five themes emerged as important in effective and culturally responsive practice by teacher educators working with Aboriginal teacher candidates. L'éducation des Autochtones au Canada a besoin de s'éloigner du modèle d'assimilation à un modèle de pédagogie adaptés à la culture. Programmes de formation des enseignants qui servent d'enseignants autochtones ont un rôle important à jouer dans le développement d'un système d'éducation qui répond à des critères à la fois traditionnels et autochtones de la réussite. Ce document examine les expériences des formateurs d'enseignants travaillant dans un baccalauréat à base communautaire autochtone du programme d'éducation qui a été développé grâce à un partenariat université-communauté. Grâce à des entrevues avec huit formateurs d'enseignants qui travaillent dans le programme, cinq thèmes ont émergé aussi important dans la pratique, efficace et adaptée à la culture par des formateurs d'enseignants travaillant avec les candidats enseignants autochtones.